ANALISIS DAYA SAING EKONOMI KREATIF DI KOTA PEKANBARU : Studi Usaha Sektor Kerajinan Galeri Batik Tabir Riau Rani - Rosmayani Rosmayani; Rosmita Rosmita; Shafira Amalia Ramadhani (UIR Press, 2020)
The purpose of the research is for beeing up the competitiveness of the creative economy in Pekanbaru city in the craft sub sector Galeri Batik Tabir Riau Rani.This research arranged in descriptive type and quantitative methods. Research data consists of primery and secondary data. Primary data obtain from observation, focused discussion, interview, and SWOT questionnaire, secondary data obtain from statistics Indonesia, literature book, journal and internet. Collected data will be analyzed with descriptive analysis and SWOT analysis techniques (Strenght, Weakness, Opportunity, Threat). From this research by way of questionnaire and fosuc discussion with the Galeri Batik Tabir Riau Rani owner,concluded that of increasing the competitiveness Galeri Batik Tabir Riau Rani it uses SO strategi, that is harnessing strength owned to get the opportunities that exist.